Adjuvant Chemoradiotherapy Versus Adjuvant Chemotherapy for Stage III Gastric or Gastroesophageal Junction Cancer After D2/R0 Resection - Shi, Jinming; Kang, Wenzhe; Tang, Yuan; Li, Ning; Jiang, Liming; Yang, Lin; Wang, Shulian; Song, Yongwen; Liu, Yueping; Fang, Hui; Lu, Ningning; Qi, Shunan; et al. (Frontiers in Oncology, 2022)
Purpose: To compare the survival benefit in the adjuvant chemoradiotherapy (CRT) group and chemotherapy (CT) group for stage III gastric or gastroesophageal junction (GEJ) cancer after D2/R0 resection. Methods and materials: From January 2011 to May 2018, 819 patients (CRT group:215 patients, CT group:604 patients) diagnosed as pathological stage III after D2/R0 resection were retrospectively collected and the survival and recurrence patterns were analyzed. The baseline characteristics were balanced based on propensity score-matching (PSM). The survival benefit was compared between two groups using Kaplan-Meier analysis and Cox regression model. Results: The five-year overall survival (OS) rate in the CRT group was significantly higher than that in the CT group whether before or after the PSM. The multivariate Cox-regression analysis identified the significant poor OS in patients with advanced TNM stage (P<0.001) and patients who didn’t receive the adjuvant CRT (P=0.008). For the recurrence patterns, 85 (39.5%) patients in the CRT group and 300 (49.7%) patients in the CT group were diagnosed as recurrence (P=0.011). The regional recurrence in the CRT group was less than that in the CT group (20.5% vs 35.1%, P=0.028). Conclusion: For patients diagnosed as stage III gastric cancer or gastroesophageal junction cancer, the addition of adjuvant chemoradiotherapy will significantly improve the overall survival and regional control.